Agenda 2030, social and work inclusion even for people with intellectual disability: ecological social and human approach - Elena Malaguti (Firenze University Press, 2019)
One of the most significant challenges for education and training of youth and adults with intellectual or complex disability deals with searching for generally accepted concepts underlying social and work inclusion. This article refers to an ecological social and human approach. Furthermore it investigates on the perspective of social and work inclusion of people with intellectual disabilities based on the main contemporary international inputs according (UN, 2006; 2015; 2018).   Agenda 2030, inclusione sociale e lavorativa anche per le persone con disabilità intellettiva: approccio ecologico sociale e umano Una delle sfide più significative per la formazione dei giovani e degli adulti con disabilità intellettiva o complessa consiste nella ricerca di approcci condivisi sottesi all'inclusione sociale e lavorativa. Il presente contributo analizza, secondo un approccio ecologico sociale ed umano, la prospettiva dell'inclusione sociale e lavorativa delle persone con disabilità intellettiva, alla luce delle principali indicazioni internazionali contemporanee (UN, 2006; 2015; 2018).